Green Synthesis of Silver Nanoparticles using Ulva intestinalis with Cytotoxic and Antioxidant Activity - Irwan Irwan; Ilham Zulfahmi; Nursafiah; Ruslaini; Eli Nurliza (Science & Technology Asia, 2024)
The cost-effective and biosafe synthesis of ”green” nanoparticles is becoming increasingly popular. Therefore, this study aimed to explore the potential of green algae (Ulva intestinalis) extract as a reducing and stabilizing agent for producing silver nanoparticles (AgNPs). U. intestinalis contains numerous secondary metabolites that play a crucial role in the formation of AgNPs. Characterization was confirmed using UV-visible spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and a particle size analyzer (PSA). The cytotoxic and antioxidant effects of the product were determined using the Brine Shrimp Lethality Test (BSLT) and 1,1-diphenyl-2 picrylhydrazyl (DPPH) assay. The results showed that the AgNPs had a spherical shape, with size variations of 4040 nm (19%), 771 nm (78.6%), and 97.3 nm (2.4%). The obtained AgNPs were found to have higher cytotoxic and antioxidant activity than the U. intestinalis extracts with an LC50 value of 128.2 𝜇g/mL (toxic category) and IC50 = 100.4 𝜇g/mL (strong category). This study proved that the AgNPs produced herein have the potential to be used for anticancer and antioxidant purposes.